2017
DOI: 10.1002/bjs.10427
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary perioperative protocol in patients undergoing acute high-risk abdominal surgery

Abstract: The introduction of a multidisciplinary perioperative protocol was associated with a significant reduction in postoperative mortality in patients undergoing AHA surgery. NCT01899885 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
162
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(176 citation statements)
references
References 47 publications
9
162
1
4
Order By: Relevance
“…19,46,[51][52][53] In the present study 34% of patients experienced postoperative pulmonary complications, which corresponds to the 36% reported for the total cohort of 600 patients who received AHA surgery following a multidisciplinary perioperative protocol. 7 Results of the present study showed that a higher proportion of patients who were nonindependently mobile on POD-7 experienced a pulmonary complication. Nonindependent patients were also more sedentary (lay or sat more) than patients who were independently mobile on POD-7.…”
Section: Physical Performancementioning
confidence: 46%
See 4 more Smart Citations
“…19,46,[51][52][53] In the present study 34% of patients experienced postoperative pulmonary complications, which corresponds to the 36% reported for the total cohort of 600 patients who received AHA surgery following a multidisciplinary perioperative protocol. 7 Results of the present study showed that a higher proportion of patients who were nonindependently mobile on POD-7 experienced a pulmonary complication. Nonindependent patients were also more sedentary (lay or sat more) than patients who were independently mobile on POD-7.…”
Section: Physical Performancementioning
confidence: 46%
“…This study is an embedded part of a larger cohort study, initiated in 2013, investigating the effect of an enhanced recovery program after AHA surgery in 600 patients (Clinicaltrials.gov: NCT01899885). 7 The larger study does not include the aim and outcomes reported in the present study.…”
Section: Study Populationmentioning
confidence: 92%
See 3 more Smart Citations